2023
DOI: 10.1021/acs.est.3c00422
|View full text |Cite
|
Sign up to set email alerts
|

Tritium and Carbon-14 Contamination Reshaping the Microbial Community Structure, Metabolic Network, and Element Cycle in the Seawater Environment

Abstract: The potential ecological risks caused by entering radioactive wastewater containing tritium and carbon-14 into the sea require careful evaluation. This study simulated seawater’s tritium and carbon-14 pollution and analyzed the effects on the seawater and sediment microenvironments. Tritium and carbon-14 pollution primarily altered nitrogen and phosphorus metabolism in the seawater environment. Analysis by 16S rRNA sequencing showed changes in the relative abundance of microorganisms involved in carbon, nitrog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…The heatmaps were drawn via TBtools [30]. The PCoA, correlation heatmaps, and RDA analysis were performed on Omicshare Tools (https://www.omicshare.com/tools/, accessed on 10 December 2023) [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…The heatmaps were drawn via TBtools [30]. The PCoA, correlation heatmaps, and RDA analysis were performed on Omicshare Tools (https://www.omicshare.com/tools/, accessed on 10 December 2023) [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…When incorporated into water molecules, tritium, a weak β emitter, can lead to organically bound tritium, which poses a greater biological risk due to its longer retention in living organisms. This aspect of tritium’s behavior in the environment and organisms is often understated . Studies have demonstrated that despite their low radiotoxicity, tritium and 14 C can cause subtle but significant biological effects.…”
Section: Radiotoxicity and Health Risksmentioning
confidence: 99%
“…Releases of radionuclides from nuclear facilities may cause negative health effects but are even more likely to trigger public concern and hence cause socioeconomic damage. , Comprehensive and reliable monitoring of anthropogenic radionuclides in the environment, therefore, is essential for nuclear safety and risk assessment of occupational exposure. Among various anthropogenic radionuclides, tritium ( 3 H) is noteworthy due to its relatively long half-life ( T 1/2 = 12.33 years) and high migration capacity. As a radioactive isotope of hydrogen, 3 H is omnipresent as tritiated water (HTO) vapor in air, leading to widespread distribution through the water cycle and food chain. Despite analytical challenges due to tritium’s volatility and low-energy beta decay, radiation regulatory authorities have extensively documented airborne HTO dynamics in many countries over the past decades. Concerning the indoor atmosphere of nuclear facilities, HTO monitoring primarily serves for surveillance monitoring to diagnose reactor status and assess occupational exposure. Although online tritium monitoring instruments (e.g., ionization chambers) provide timely information in case of accidental leakage, the high instrument costs, high detection limits, and single-point radiation measurement limit their ability to characterize the spatiotemporal heterogeneity of HTO in large volumes of indoor air, such as reactor halls. , Without exact and quantitative knowledge on HTO in air, small leakages from nuclear installations cannot be pinpointed accurately, and the development of proper strategies for nuclear facility decommissioning may also influenced. Therefore, a supplementary method for the comprehensive characterization of HTO vapor in nuclear facilities is desired to meet future challenges resulting from nuclear power expansion based on both fission and fusion.…”
Section: Introductionmentioning
confidence: 99%